Restoring forest resilience: From reference spatial patterns to silvicultural prescriptions and monitoring - Churchill, Derek J.; Larson, Andrew J.; Dahlgreen, Matthew C.; Franklin, Jerry F.; Hessburg, Paul F.; Lutz, James A. (Forest ecology and management, 2013)
► We quantified stand-level pattern in terms of individual trees, clumps, and openings. ► We used AET and Deficit to develop climate analog reference conditions. ► We developed a method to translate reference patterns into prescription guidelines. ► Our ICO method created patterns in agreement with reference conditions. ► Reference spatial patterns offer a proven resilience strategy. Stand-level spatial pattern influences key aspects of resilience and ecosystem function such as disturbance behavior, regeneration, snow retention, and habitat quality in frequent-fire pine and mixed-conifer forests. Reference sites, from both pre-settlement era reconstructions and contemporary forests with active fire regimes, indicate that frequent-fire forests are complex mosaics of individual trees, tree clumps, and openings. There is a broad scientific consensus that restoration treatments should seek to restore this mosaic pattern in order to restore resilience and maintain ecosystem function. Yet, methods to explicitly incorporate spatial reference information into restoration treatments are not widely used. In addition, targets from reference conditions must be critically evaluated in light of climate change. We used a spatial clump identification algorithm to quantify reference patterns based on a specified inter-tree distance that defines when trees form clumps. We used climatic water balance parameters, downscaled climate projections, and plant associations to assess our historical reference sites in the context of projected future climate and identify climate analog reference conditions. Spatial reference information was incorporated into a novel approach to prescription development, tree marking, and monitoring based on viewing stand structure and pattern in terms of individuals, clumps, and openings (ICO) in a mixed-conifer forest restoration case study. We compared the results from the ICO approach with simulations of traditional basal area and spacing-based thinning prescriptions in terms of agreement with reference conditions and functional aspects of resilience. The ICO method resulted in a distribution of tree clumps and openings within the range of reference patterns, while the basal area and spacing approaches resulted in uniform patterns inconsistent with known reference conditions. Susceptibility to insect mortality was lower in basal area and spacing prescriptions, but openings and corresponding opportunities for regeneration and in situ climate adaptation were fewer. Operationally, the method struck a balance between providing clear targets for spatial pattern directly linked to reference conditions, sufficient flexibility to achieve other restoration objectives, and implementation efficiency. The need to track pattern targets during implementation and provide immediate feedback to marking crews was a key lesson. The ICO method, especially when used in combination with climate analog reference targets, offers a practical approach to restoring spatial patterns that are likely to enhance resilience and climate adaptation.